Evaluation of clinical efficacy and safety of "Yesaka Liquid" (an ayurvedic liquid formulation) as add-on therapy to oral hypoglycemic agents in type ii diabetes patients - Pawankumar Godatwar; Shailesh Deshpande; Sanjay Tamoli; Shishir Pande; Amol Hartalkar; Abhay Kulkarni; Payjani Dubey; Swapnali Mahadik; Vinay Pawar (Wolters Kluwer Medknow Publications, 2022)
Introduction: Yesaka Liquid is an Ayurvedic Proprietary formulation containing multiple standardized herbal extracts like Triphala (3 myrobalans), Jamun (Eugenia jambolana), Kutki (Picrorhiza kurrooa), Haridra (Curcuma longa) etc., having potential anti-diabetic and anti-oxidant properties. The evaluation of clinical efficacy and safety of Yesaka Liquid as an Add-on therapy to oral hypoglycemic agents (OHAs) in Type II diabetics was the primary objective of the study. Methods: After obtaining ethical approval and informed consent, at five study sites, 112 patients were randomized in two study groups. The patients in Add-on Group were given Yesaka Liquid along with OHAs while those in the Control Group were asked to continue with the on-going OHA (s) for 90 days. The assessment of efficacy was done by estimation of HbA1c%, quality of life (QOL) on WHO-QOL BREF questionnaire, plasma glucose, serum insulin, symptoms of diabetes mellitus, anthropometric measurements, and changes in homeostatic model assessment for insulin resistance score. The assessment of safety was done by clinical review of all safety parameters and safety-related laboratory parameters. Global assessment of overall safety and tolerability by the physician and patient was also done. Results: Yesaka liquid was found to be effective as add-on therapy to OHAs in type II DM management by controlling the levels of HbA1c and blood sugar. It showed significant effect in reducing various symptoms of type II DM and also improved the QOL of patients. Conclusion: Yesaka Liquid can be recommended as an effective and safe formulation for the management of type II DM as an odd-on therapy.